PENGARUH STRUKTUR MODAL, NET PROFIT MARGIN (NPM), CURRENT RATIO (CR), DAN PRICE EARNING RATIO (PER) TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2017 - Santi Warwati Simanjuntak; Herianto Sipayung; Annisa Nauli Sinaga; Jaka Permana; Thomas Firdaus Hutahaen (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Investment is one of the tools used by many investors or shareholders to maintain their wealth. That is by way of investing its shares in the capital market. The hope of obtaining maximum returns is very important for investors to evaluate financial statements for information related to how investors can easily make investment decisions. This study aims to look at the effect of Capital Structure, Net Profit Margin, Current Ratio, and Price Earning Ratio on Stock Returns in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period 2014-2017. Determination of samples using purposive sampling method and the samples studied were 23 companies. Data analysis method using multiple regression analysis.